A rare case of pastel dilution in Trogon elegans (Aves: Trogonidae) from Reserva de la Biosfera El Cielo, Mexico - Ruiz, Erick Ruben (2022)
The bird abnormal colorations are rare and poorly documented. They had been related to congenital problems and external factors, considered as an ambiental indicator that gives evidence and clues about the quality of the populations at a genetic level. We identified a pigmentary abnormalitycase on a Elegant Trogon (Trogon elegans (Gould, 1834)) in the natural protected area “Reserva de la Biosfera El Cielo”, Mexico. We determined the type as pastel dilution, on this mutation both melanin are greatly affected, where it lacked melanin, but it kept the carotenoids with the rd color on the ventral feathers. We discuss posible explanations for this abnormal coloration and asume that it was due to genetic or developmental alterations of the individual that caused the bleaching of the plumage.